Boosting Creativity in Writing German Descriptive Texts with Project-Based Learning - Anim Purwanto; Ninuk Lustyantie; Muhammad Kamal bin Abdul Hakim (Malikussaleh University, Aceh, Indonesia, 2025)
This research is motivated by the low ability of students to write descriptive texts in German, which is largely caused by the use of conventional learning methods and limited active student involvement in the learning process. The aim of this study is to improve students’ writing skills through the implementation of PjBL that emphasizes collaborative and reflective project activities. This classroom action research was conducted in two cycles, involving 36 eleventh-grade students as subjects. Data collection techniques included observations of student activities and descriptive text writing tests, while data analysis was carried out using both quantitative and qualitative descriptive approaches by comparing learning outcomes between cycles. The results indicated a significant improvement in students’ writing performance: the average score increased from 65 in cycle I to 82 in cycle II, while the completion rate rose from 30.56% to 86.11%. Observational data revealed that students actively engaged in group discussions, confidently expressed ideas, responded to peer feedback, and demonstrated higher motivation in completing writing tasks. Furthermore, the quality of their descriptive texts improved, particularly in terms of structure, vocabulary, grammar accuracy, and creativity. These findings suggest that the PjBL model effectively enhances not only students’ descriptive writing skills but also their collaboration, critical thinking, and creative expression. The study theoretically contributes to the growing literature on PjBL in foreign language education, providing evidence of its impact on student learning outcomes. Practically, the findings serve as a valuable reference for teachers aiming to develop innovative, student-centered, and effective strategies for teaching descriptive writing in German, promoting active learning and sustained engagement in the classroom